VITAMIN AND MINERAL CORRECTION IN PUBERTAL PERIOD - S.V. Talashova ("Paediatrician" Publishers LLC, 2009)
This article describes a role of calcium, phosphorus, vitamins D, A and group of vitamins B in growth and development of adolescents. Balances composition of complex medication «Kalcinova» allow preventing of deficient state in children in prepubertal period.Key words: adolescents, calcium, vitamins, nutrition.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(3):120-122)